Root Temperature Variation during Gutta-Percha Removal Using Stainless Steel and NiTi Instruments - Fernanda Clotilde Mariz Suassuna; Ana Marly Araújo Maia Amorim; Saulo Leonardo Sousa Melo; Diego Filipe Bezerra Silva; Layrlla Kateriny Moura Oliveira Lopes; Patrícia Meira Bento; Daniela Pita de Melo (Association of Support to Oral Health Research (APESB), 2024)
Objective: To assess the temperature variation of gutta-percha removal with stainless steel and two NiTi instruments using infrared thermography and thermocouples. Material and Methods: 45 single-rooted teeth were divided into three groups (n = 15) according to the following gutta-percha removal instruments: Largo Peeso (L), Protaper Retreatment (PR), and Reciproc (R). Thermal analysis was conducted using a FLIR T650sc infrared thermography camera and three thermocouples. For infrared thermography assessment, the infrared camera was programmed to acquire thermograms every 15 seconds before the gutta-percha removal started until temperature normalization. Root temperature was assessed in the thermograms using FLIR tools software v6.4 with the straight-line tool along the long axis of the tooth and in the cervical, middle, and apical thirds of each tooth. The temperature from the thermocouples was recorded and registered for each root third. Inferential statistical analysis Kruskal-Wallis and post hoc Tukey tests were used. Results: For the infrared thermography camera, the highest median temperature value was found 15 seconds after gutta-percha removal for the L technique (20.3°C), which presented the highest temperatures at all studied times. For thermocouples, the highest temperature was found in the middle third during gutta-percha removal with L (20.7°C). PR and R presented similar patterns of root temperature. Conclusion: Stainless-steel L temperature reaches values above 10°C; however, the exposure time was too short to cause injuries to the periodontium.